La distribución geográfica de las razas de Lophonetta specularioides y Merganetta armata (Anatidae) en las provincias de Mendoza y San Juan, Argentina - Navas, Jorge R. (1998)
On the basis of five specimens at the MACN collection, the population of Lophonetta specularioides from the province of Mendoza seems somewhat intermediate between northern birds (subsp. alticola) and southern birds (Subsp, specularioides). Based on specimens of Merganetta a. armata we extend the distribution of this subspecies northward by about 320 km in the province of San Juan.